Self-healing in mortars: rules of selection of healing agents - Escobar, Mariano Martin (2013)
In the present work key parameters of different epoxy systems (such as viscosity and gel time) were evaluated to be used as healing agents when were included in a cement matrix. Epoxy systems were encapsulated in hollow glass tubes and were introduced in a mortar matrix. Samples were preloaded under three point bending in order to create a crack and release the healing system. After that, they were loaded to measure the residual strength and estimate the healing efficiency. The influence of temperature and the volume of the glass tubes were examined. Regarding the healing efficiency, a higher temperature led to an improvement of autogenous healing of the mortar matrix and a higher degree of crosslinking of the healing agent. For the studied systems, the use of glass tubes with smaller diameter containing the healing system seemed to be better in order to maintain the mechanical properties of the mortar-based composite.